FUNDAMENTALS OF IMPROVING METHODOLOGICAL TRAINING OF FUTURE PRIMARY TEACHERS (World Bulletin of Social Sciences, 2024)
In the article improving the methodological training of future primary school teachers improving the quality of education based on its content, form and methods, theoretical, practical and educational importance, the ability to use them in a coherent manner in teaching students natural science materials as one of the important factors of educational effectiveness the essence of the lessons organized on the basis of the methodical preparation of the class teacher, as well as the infrastructure of its improvement are presented.